Identifying multiple outliers in linear regression : Robust fit and clustering approach - Adnan, Robiah; Setan, Halim; Mohammad, Mohd. Nor (2001)
This research provides a clustering based approach for determining potential candidates for outliers.This is a modification of the method proposed by Serbert et.al (1998).It is based on using the single linkage clustering algorithm to group the standardized predicted and residual values of data set fit by least trimmed of squares (LTS).